Preoperative hyponatremia and survival after left ventricular assist device implantation. Issue 9 (16th May 2022) - Lamba, Harveen K.; Parikh, Umang M.; Vincent, Justin; Civitello, Andrew B.; Nair, Ajith; Bhardwaj, Anju; Senussi, Mourad H.; Loor, Gabriel; Shafii, Alexis E.; Liao, Kenneth K.; Chatterjee, Subhasis
Abstract: Background: Hyponatremia is associated with adverse outcomes in heart failure and after cardiac surgery. We hypothesized that hyponatremia is associated with poorer short‐term and longer term survival in patients after continuous‐flow left ventricular assist device (CF‐LVAD) placement. Methods: We reviewed a single‐center database of patients who received a CF‐LVAD during 2012–2017. Sodium (Na) values obtained within 14 days before CF‐LVAD insertion were averaged; patients ( n = 332) were divided into hyponatremia (mean Na <135 mEq/L; n = 160; 48.2%) and normonatremia groups (mean Na 135–145 mEq/L; n = 172; 51.8%). Patients requiring preoperative dialysis or pump exchange were excluded. We compared outcomes between preoperative hyponatremia and normonatremia groups. Results: The two groups' baseline characteristics were similar, although hyponatremia patients more often had preoperative mechanical circulatory support (44.4% vs. 31.4%, p = 0.002). Although hyponatremic and normonatremic patients did not differ in 30‐day mortality (7.5% vs. 6.5%, p = 0.7), preoperative hyponatremia was associated with greater 5‐year mortality (61% vs. 44%, p = 0.03). On binary logistic regression analysis, the strongest independent predictors of late mortality were hyponatremia (odds ratio [OR] 1.88, 95% CI [1.07–3.31], p = 0.02), older age (OR 1.03, 95% CI [1.01–1.05], p = 0.01), and elevated mean right atrial pressure/pulmonary capillary wedge pressure ratio (OR 4.69, 95% CI [1.76–12.47], p = 0.002). Conclusions: Hyponatremia was not associated with greater early mortality but was associated with poorer late survival. The optimal timing of LVAD implantation in relation to hyponatremia, and whether correcting hyponatremia perioperatively improves long‐term survival, should be investigated. Abstract : Comparing LVAD recipients with preoperative hyponatremia demonstrated no major differences in early outcomes but reduced late survival in the hyponatremia patients.